Replies: Income Distribution In Peru. About The Book Of R. Webb And A. Figueroa - Gómez Camacho, Francisco (1977)
We present a comment of Francisco Gómez Camacho al libro de Richard Webb y Adolfo Figueroa, Income Distribution In Peru (Lima, Instituto de Estudios Peruanos, 1975), and a response from Adolfo Figueroa.